Strategy For Sustainable Development and Feed Processing Technology Using Chopper Machine for Goat Farming in Dolok Ilir I Simalungun Regency - patriani, peni patriani (Journal of Saintech Transfer, 2024)
Sustainable development in animal husbandry through feed processing technology using modern machines is needed to increase the productivity of goats in Dolok Ilir I, Dolok Batu Nanggar District, Simalungun Regency. The problems faced by the service partners include maintenance management and preparation of animal feed that could be more optimal, thus reducing the productivity of goats. In addition, technology in the form of automatic equipment or machines and housing management for incentive management is also needed. Some solutions to problems are the Assisted Village Service Team conducting activities in the form of 1) Training on feed preparation and making herbal nutritional supplements for goats, 2) Provision of goat feed production machines and training in the use of chopper machines, 3) Construction of goat cages for intensive management. The service method applied is using media in the form of banners and training practices. Training practices are carried out by providing material and demonstrations on preparing feed, making herbal nutritional supplements, and operating a grass chopper machine. The results of the activities that have been carried out show an increase in farmers’ knowledge and skills related to making feed preparation, making herbal nutritional supplements and operating chopper machines with an achievement rate of 95%. Science and technology in community service activities have been applied by farmers so that they can increase the sustainable development of animal husbandry in the Fostered Village. The participation of village officials also supports the progress of livestock development in the Assisted Village of Dolok Ilir, Simalungun Regency.